Emails From Our Good Friend Jonathan Harker : Dracula Daily’s Effect on The Reader Experience of Dracula and the Dynamics of Fandom on Tumblr - Martinez Ziegler, Samantha (My University, 2024)
Dracula Daily is a Substack newsletter created in 2021 that delivers Bram Stoker’s epistolary novel Dracula (1897) in chronological order and in a serialised format to its subscribers through email over the span of six months. The newsletter gained popularity during its 2022 edition, gathering over 200.000 subscribers reading along. Dracula Daily became a phenomenon on social media, particularly on the microblogging platform Tumblr, where a dynamic online fan community was born. This dissertation aims to examine the role of Dracula Daily in shaping the reader and online fan experience of Dracula, identify the elements that affect the reader engagement with the novel, and further the research in online fandom and present-day Tumblr fan culture. This dissertation uses the May-November 2022 period of activity of the Dracula Daily fandom on Tumblr as its case study. Over the course of six months, Tumblr posts found in the Dracula Daily tag page were collected in a private Tumblr blog. A total of 543 posts served as research material. The research methods used to treat and analyse the data are a mixed methodology based on participant observation and qualitative content analysis. The findings of this research point that Dracula Daily positively influenced the way fans collectively produced new meanings out of the novel. The six-month period of activity showed a thriving virtual community of readers that engaged in lively conversations, discussions, and analyses, and in the production of transformative works. Based on the qualitative analysis of the data and in reference to the participant knowledge gained, this study determines that there are three main elements that affected the reader experience of the novel: the change in chronology, the serialisation of the text, and modern fan culture. Each of these elements has a unique influence in the way the novel is presented and, therefore, interpreted by the readers. This dissertation concludes that the digital storytelling format implemented by Dracula Daily helps bridge the gap between classic literature and modern audiences.
Keywords: dracula daily, fandom, dracula, fan culture, tumblr, participatory culture, digital storytelling